2016
DOI: 10.1021/acsami.6b10395
|View full text |Cite
|
Sign up to set email alerts
|

Highly Anisotropic Adhesive Film Made from Upside-Down, Flat, and Uniform Vertically Aligned CNTs

Abstract: We have created a multifunctional dry adhesive film with transferred vertically aligned carbon nanotubes (VA-CNTs). This unique VA-CNT film was fabricated by a multistep transfer process, converting the flat and uniform bottom of VA-CNTs grown on atomically flat silicon wafer substrates into the top surface of an adhesive layer. Unlike as-grown VA-CNTs, which have a nonuniform surface, randomly entangled CNT arrays, and a weak interface between the CNTs and substrates, this transferred VA-CNT film shows an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
11
0
5
Order By: Relevance
“…Nevertheless, considering the difficulty in engineering synthesis of large-area and high-quality graphene, so far, there is little practical application of industrially produced graphene. Consequently, it is worth focusing on allotropes of graphene [11,12,13], which are more stable and feasible to produce. Recently, a stable carbon allotrope, namely, carbon honeycomb (CHC), a three-dimensional graphene, was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, considering the difficulty in engineering synthesis of large-area and high-quality graphene, so far, there is little practical application of industrially produced graphene. Consequently, it is worth focusing on allotropes of graphene [11,12,13], which are more stable and feasible to produce. Recently, a stable carbon allotrope, namely, carbon honeycomb (CHC), a three-dimensional graphene, was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…This friction can originate from microscale asperities, rough surface features, or specially engineered surface morphologies 37,38 . Therefore, friction coefficient can increase depending on the specific choice of material or specially engineered surfaces 39 .…”
Section: Methodsmentioning
confidence: 99%
“…[40] Unlike randomly dispersed CNT/polymer nanocomposites, the alignment of CNTs in a polymer matrix can provide anisotropic conducting paths along the direction of heat and electric transport, facilitating the fabrication of soft actuators with good mechanical output. [41] Therefore, composite actuators with anisotropic CNT alignment have attracted significant attention. Li et al reported a flexible actuator based on superoriented CNT paper and polymer film.…”
Section: Introductionmentioning
confidence: 99%